Tutela judicial a un ambiente sano, desde el principio de especialidad en el Ecuador - Pozo, Francisco P. (2023)
Effective judicial protection of a healthy environment in Ecuador is a challenge that requires a specialized approach. This study analyzes the application of the specialty principle to guarantee environmental protection through a suitable environmental jurisdiction. A documentary review of environmental legislation in Ecuador and the constitutional recognition of the rights of nature was carried out. The findings indicate that judicial specialization in environmental law is essential to resolve disputes related to biodiversity conservation and the preservation of natural resources. It is concluded that the principle of specialty, embodied in the creation of environmental courts, is essential to ensure access to justice and the effective protection of a healthy environment. It is recommended to strengthen judicial specialization in environmental matters to protect the natural environment and promote intergenerational equity.